Leadership: A Strategic Tool For Enhancing Employee Work Performance (Journal of Namibian Studies : History Politics Culture, 2023)
This research paper explores the importance of leadership in work performance. Through a review of existing literature and studies, the paper examines the different leadership styles that are effective in enhancing work performance, the impact of leadership on employee motivation, and the relationship between leadership and employee job satisfaction. The findings show that effective leadership styles, such as transformational, transactional, and servant leadership, play a significant role in enhancing work performance. Additionally, the research highlights the importance of the relationship between leadership and employee motivation and job satisfaction in enhancing work performance. Organizations that invest in leadership development and create a work environment that fosters employee engagement and collaboration are more likely to achieve their goals and objectives. A literature review was conducted to examine previous research on leadership and work performance, and the findings suggest that transformational leadership has a positive effect on work performance, while laissez-faire leadership has a negative impact. The research also found that transactional leadership can have a mixed effect on work performance depending on the situation.